2015
DOI: 10.1039/c4nj02040e
|View full text |Cite
|
Sign up to set email alerts
|

1-Naphthylamine functionalized Pt nanoparticles: electrochemical activity and redox chemistry occurring on one surface

Abstract: We present the preparation and electrochemical application of Pt nanoparticles (Pt NPs) functionalized with 1-naphthylamine. Under electrochemical conditions, Pt surface bound 1-naphthylamine (NA) can be reversibly switched (oxidized and reduced), while simultaneously electrocatalytic reactions (e.g. CO oxidation) can proceed on the Pt surface. While the redox activity of the ligand is established immediately after functionalization, the functionalized NPs have to be stored as a colloidal dispersion in tetrahy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…However, as the particles remain CO‐covered – CO is naturally formed by the catalytic process at the NP surface via organic solvent oxidation – sintering is mainly prevented. After washing with 1 M HCl (removing residual EG) “surfactant‐free” NPs are received as CO‐covered NPs that can be re‐dispersed in various organic solvents (e. g. pure EG, acetone, tetrahydrofuran or cyclohexanone, see Figure S1) ,…”
Section: Resultsmentioning
confidence: 99%
“…However, as the particles remain CO‐covered – CO is naturally formed by the catalytic process at the NP surface via organic solvent oxidation – sintering is mainly prevented. After washing with 1 M HCl (removing residual EG) “surfactant‐free” NPs are received as CO‐covered NPs that can be re‐dispersed in various organic solvents (e. g. pure EG, acetone, tetrahydrofuran or cyclohexanone, see Figure S1) ,…”
Section: Resultsmentioning
confidence: 99%
“…The use of capping agents, such as surfactants, organic ligands, or dendrimers, is mandatory for the synthesis of stable colloidal metal nanoparticles (NPs), as they compensate the high surface energy of the NPs and protect them from aggregation. , Nevertheless, it has also been reported that the capping agents used in colloidal synthesis are not merely stabilizers but also effective additives which modify the final NPs morphology features, not only in terms of NPs size and shape, but also in terms of electronic properties. Thus, despite this necessity, the impact of these molecules once the metal NPs are synthesized is a difficult issue, as it will affect the catalytic behavior of metal-based catalytic systems by modifying either the NPs physicochemical properties or their accessibility by creating a physical barrier that hinders the access of reactants to the catalytically active sites on the surface of the NPs. , In this respect, the accessibility to the NP surface is strongly dependent on the molecular structure of the capping agent, as it will determine its conformation once adsorbed on the metal surface. ,, …”
Section: Introductionmentioning
confidence: 99%
“…10,11 In this respect, the accessibility to the NP surface is strongly dependent on the molecular structure of the capping agent, as it will determine its conformation once adsorbed on the metal surface. 1,12,13 Due to its high protecting value, non-toxicity and solubility in many polar solvents, poly-n-vinylpyrrolidone (PVP) is one of the most common and widely studied capping agents in the synthesis of metal NPs. 2,[14][15][16] PVP has been proven to modify the NPs electronic properties through a charge transfer between the polymer functional groups and the metal surface.…”
Section: Introductionmentioning
confidence: 99%
“…The result of this steric challenge is a more opened 113.3 C Me (eclipsed)-N-C Ar (non-protonated) bond angle and two correspondingly compressed 109.8 C Me (staggered)-N-C Ar (nonprotonated) bond angles ( Figure 1). Furthermore, 10's angular compression is further exacerbated by its shorter 1.495 Å C(sp 2 )-+ NMe 3 bond length 6 versus the longer 1.596 Å C(sp 3 )-+ NMe 3 bonds 7 in the diamantane-4,9-di(NMe 3 I), 1 crystal structure (Refcode TOCMEF), see Figure 1. Now, C(sp 3 )hybridization at the bridgehead-C(4 or 9) of crystalline 1 enabled all three N-CH 3 bonds to be staggered relative to the three vicinal C Diam (sp 3 -quat)-C(methylene) bonds, and thereby produced more stable 111.4(5) C Me (staggered)-N-C Diam (quat.)…”
Section: Synthesis Of Compoundsmentioning
confidence: 99%
“…The naphthalene compounds are of on-going interest in our group. 3 It is well known that naphthalene amines have many applications and they are useful in many fields, such as in assisted laser desorption/ionization mass spectrometry for imaging of small molecules in tissues, 4 as a part of conducting polymer as a matrix for biomolecule immobilization, 5 in the preparation of functionalized Pt nanoparticles for study of electrochemical activity and redox chemistry occurring on one surface, 6 in naphthylamine-based organic photovoltaic cells, 7 as well as for reductive electron transfer to DNA. 8 For these reasons we believe that it is important to improve known, or develop new, synthetic methods to make these compounds easily accessible.…”
Section: Introductionmentioning
confidence: 99%